The use of hemodialysis in hypercalcemic crisis secondary to primary hyperparathyroidism - Marouço,Catarina Nazário (2021)
ABSTRACT Severe hypercalcemia can be either acute or decompensate from a chronic state to a medical emergency, the hypercalcemic crisis. The presence of symptoms such as altered mental status or potentially fatal ECG abnormalities demand an expeditious decrease in serum calcium levels. Standard medical therapy consists of vigorous volume replacement, calcitonin and, depending on the etiology, bisphosphonates, cinacalcet or glucocorticoids. Hypercalcemic crisis is a rare indication for urgent hemodialysis and is reserved for patients with severe symptoms, ineffective medical therapy or end stage renal disease. The use of hemodialysis in this scenario is not commonly reported. We hereby report a patient who presented with altered mental status and acute kidney injury due to a hypercalcemic crisis secondary to primary hyperparathyroidism. Treatment included urgent hemodialysis to effectively lower calcium levels.